MRI in CLN2 disease patients: Subtle features that support an early diagnosis. (September 2020) - Aydın, Kürşad; Havali, Cengiz; Kartal, Ayşe; Serdaroğlu, Ayşe; Haspolat, Şenay
Abstract: Neuronal ceroid lipofuscinosis type 2 (CLN2) disease is a rare, paediatric-onset, neurodegenerative disorder characterised in its early stages by language delay, seizures and loss of motor function. It is rapidly progressive and ultimately results in the premature death of patients. We aim to highlight common magnetic resonance imaging (MRI) features seen in early CLN2 disease and increase disease awareness among clinicians in order to facilitate early diagnosis and treatment of patients with disease-modifying enzyme replacement therapy. We obtained MRI scans from 12 Turkish children with CLN2 disease, at symptom onset or time of diagnosis, and at various times during disease progression. Patient details including age at onset of symptoms, age at diagnosis and clinical presentation were collected. MRIs were analysed to identify common features present in patients with CLN2 disease. The median diagnostic delay in this cohort was 2 years, highlighting the need for increased disease awareness among clinicians. Key MRI features suggestive of CLN2 disease that were identified included cerebellar atrophy in 11 patients, linear hyperintensity of central white matter in 10 patients, cerebral atrophy in 8 patients and thinning of the corpus callosum in 6 patients. Thalamic hypointensity was seen in 1 patient and may also indicate CLN2 disease. It is important to consider the presenting symptoms alongside clinical test results in order to support early diagnosis of CLN2 disease. Clinical suspicion of CLN2 disease accompanied by the detection of any of the above-mentioned features on MRI should encourage healthcare professionals to test for CLN2 disease. Highlights: Subtle MRI features may be used to facilitate early diagnosis of CLN2 disease. The most common MRI feature reported was cerebellar atrophy. Other MRI features were central white matter hyperintensity and cerebral atrophy. Clinical suspicion and MRI features should encourage testing for CLN2 disease.